Building Trust in AI Systems: The Role of Transparency and Accountability (Journal of responsible AI & ethics, 2026)
As Artificial Intelligence (AI) continues to transform various sectors, ensuring trustworthiness in AI systems has become a critical issue. The role of transparency and accountability is central to building trust in these systems, as stakeholders—from consumers to regulators—demand greater insight into how AI algorithms make decisions. This paper explores the importance of transparency and accountability in fostering trust in AI systems, focusing on the mechanisms that can be put in place to ensure these principles are upheld. The paper examines the ethical implications of AI transparency, such as the need for explainable AI (XAI), and the responsibility of AI developers and companies to disclose their decision-making processes. Through an exploration of current regulatory frameworks, case studies, and industry practices, this paper identifies challenges and provides recommendations for designing AI systems that are both transparent and accountable. The findings suggest that adopting transparent practices not only improves public trust but also mitigates bias and unintended consequences, ultimately fostering responsible AI development and use.